DIP2B Interacts With α-Tubulin to Regulate Axon Outgrowth - Xing, Zhen-Kai; Zhang, Lu-Qing; Zhang, Yu; Sun, Xue; Sun, Xiao-Lin; Yu, Hua-Li; Zheng, Yao-Wu; He, Zi-Xuan; Zhu, Xiao-Juan (Frontiers in Cellular Neuroscience, 2020)
Axonal development is essential to the establishment of neuronal morphology and circuitry, although the mechanisms underlying axonal outgrowth during the early developmental stages remain unclear. The conserved disco-interacting protein B (DIP2B) consists of a DMAP1 domain and two adenylate-forming domains (AFDs). Here, we describe how DIP2B is highly expressed in the excitatory neurons of the hippocampus. DIP2B knockout led to abundant axonal developmental outgrowth but not polarity at an early developmental stage. The loss of DIP2B inhibited synaptic transmission for both spontaneous and rapid release in cultured hippocampal neurons. Furthermore, DIP2B function during axonal outgrowth required tubulin acetylation. These findings reveal a new conserved regulator of neuronal morphology and provide novel intervention mechanisms for neurocognitive disorders.